Preservation of Anti-cytomegalovirus Activity in Human Milk Following High-Pressure Processing Compared to Holder Pasteurization - Kothari, Akash; Pitino, Michael A.; Unger, Sharon; Perreault, Véronique; Doyen, Alain; Pouliot, Yves; McGeer, Allison J.; Stone, Debbie; O’Connor, Deborah L. (Frontiers in Nutrition, 2022)
Pasteurized donor human milk is recommended for hospitalized preterm infants when mother’s own milk is unavailable. Our aim was to compare the antiviral activity of human milk processed by Holder pasteurization (HoP) or high pressure processing (HPP) against representative enveloped and non-enveloped viruses including cytomegalovirus and hepatitis A virus. Expressed milk from 20 donors collected from the Ontario Milk Bank was combined into 10 pools, each from two unique donors. Each pool was processed by HoP (62.5°C, 30 min) or HPP (500MPa, 8 min, 4°C) and subsequently inoculated with cytomegalovirus or hepatitis A virus to achieve a final concentration of 5-log plaque forming units/mL. Plaque reduction assays were used to quantify detectable virus after 30 min incubation (room temperature). Post-hoc experiments using a 4-hour incubation time were conducted if reductions were detected at 30 min. Irrespective of processing, cytomegalovirus concentrations declined in all pools after 30 min incubation (P < 0.0001). Milk processed by HoP exhibited significantly less reduction compared to raw milk (P = 0.0069). In post-hoc experiments, anti-cytomegalovirus activity was maintained at 4 hours, with high inter-pool variability. Hepatitis A virus concentration remained unchanged after 30 min incubation in raw and processed milk. Anti-cytomegalovirus activity in human milk is preserved following HoP and HPP, persisting up to 4 hours post-inoculation; anti-hepatitis A virus activity was not observed in raw or processed milk. Further research is needed to understand how HoP or promising alternative processing methods affect antiviral activity of donated milk, given its potential importance to recipient infants.